Method development and validation of dissolution of obeticholic acid tablets by RP-HPLC - C.MOUNICA; DR.S.SHOBHA RANI; B.NAGA MALLESWARI (International Journal of Pharma and Bio Sciences, 2019)
Obeticholic acid is a potent Farnesoid X receptor agonist. The main objective of the study is to develop a sensitive and reliable method for the estimation of percentage drug release in obeticholic acid tablets. This method is accurate and sensitive. A specific and precise RP-HPLC method has been developed and validated for measuring the drug release in Obeticholic acid tablet formulation by using refractive index detector. An isocratic separation was achieved in RI detector using an Accucore C18, (50*4.6mm, 2.6µm) column with pH 3.0 KH2PO4 buffer and ACN (50:50v/v) respectively at a flow rate of 0.8ml/min with refractive detector sensitivity of 256. The column temperature was maintained at 45oC. The injection volume was 100µl and the run time was maintained for 10 minutes. The method was validated for specificity, linearity, precision, accuracy and robustness. The method was linear over the range from 0.6ppm to 18.0ppm. The accuracy was between 96.1 and 100.2%.The method was found to be precise, accurate, and linear which can be used for the determination of drug release in Obeticholic acid tablets.